Sand dunes Changes in Boa Viagem Beach - Recife (PE) originated by Anthropogenic Action - João italiano de Carvalho Rocha (Investigaciones Geográficas, 2018)
The dune environment with vegetation in the coastal region has become one of the areas of the geographic space that suffers most with poorly planned anthropogenic action, being exposed to the degradation of its natural components. The preservation of the frontal dune strands is still considered the best solution to prevent a region of coastal erosion. To obtain the theoretical data of the research was used as a search engine the Google site and the field images were obtained by remote sensing. The beach arch of Praia de Boa Viagem can be described as a system dominated by waves and winds, agents responsible for the sedimentary dynamics and modelers of the coastline. There was a significant loss of dunes with vegetation cover accelerated by anthropic action. It is concluded that there is a need to implement an adequate recovery management of the degraded area that increases its extension there each year. The aim of this study was to understand the consequences of anthropic action in the natural environment of Boa Viagem beach, Recife-PE.